Genesis of Czech Decadence and Symbolism Towards Theurgy - VOREL , Jan (Bohemistyka, 2020)
The article is focused mainly on metamorphoses of aesthetic-philosophical approaches of the most important representatives of Czech literature at the end of 19th and beginning of 20th century whose work presents gradual heading for modern art, from decadent to symbolist focus using an aesthetic theory of Russian philosopher Vladimir Solovjov based on theurgic substance of art.